TEACHING WRITING RECOUNT TEXT BY USING A TOPICAL APPROACH TO THE EIGHTH-GRADE STUDENTS’ STATE OF JUNIOR HIGH SCHOOL NUMBER 42 OF PALEMBANG - Cindy Maharani; Mulyadi; Herlina (Esteem Journal of English Education Study Programme, 2024)
This research evaluates the effectiveness of a topical approach in teaching recount text writing to eighth-grade students at State of Junior High School number 42 of Palembang. Employing a quantitative pre-experimental design, the study sampled 34 students who underwent pre-tests and post-tests to measure their writing abilities. The findings indicated a significant improvement in the students' writing skills after using the topical approach. The average pre-test score was 52.5, with scores ranging from 31 to 68.5. After the intervention, the average post-test score increased to 75.7, with a range from 53 to 92.5. The t-test analysis revealed a t-obtained value of 13.31, surpassing the critical value of 1.692, leading to the rejection of the null hypothesis and acceptance of the alternative hypothesis. During the pre-test, students struggled with idea generation and grammatical accuracy. Post-intervention results showed that students became more adept at generating ideas, using correct grammar, narrating experiences, and expanding their vocabulary. Thus, the topical approach proved effective in enhancing recount text writing skills among the eighth grade State of Junior High School Number 42 of Palembang.